Influence of Neighborhood Characteristics on Physical Activity, Health, and Quality of Life of Older Adults: A Path Analysis - Liu, Zhengying; Kemperman, Astrid; Timmermans, Harry (Frontiers in Public Health, 2021)
Background: As life expectancy and health expenditure consumed by older people increase, maintaining a better health and quality of life for older adults has become an important social issue. Research indicates that physical activity may help address this challenge. Moreover, it is believed that improved quality of life and health benefits from physical activity can be achieved through interventions in the neighborhood environments. However, existing knowledge has often been based on bivariate relationships between these factors, and few studies have formally examined the extent to which any association between neighborhood environments, health, and quality of life may be mediated by the level of physical activity. This paper aims to investigate the direct and indirect influence of neighborhood characteristics on the health and quality of life of older adults, taking into account physical activity behavior and socio-demographic characteristics in a more comprehensive framework. Methods: Data were collected using a survey among 363 older adults aged 60 years and over in China. A path analysis was used that derives all direct and indirect relationships between the variables. Results: Leisure-time physical activity levels played a mediating role in the relation between social capital and health as well as quality of life. Moreover, the study confirmed direct relationships between neighborhood characteristics such as neighborhood aesthetics and traffic safety and health as well as quality of life. However, the effect of neighborhood characteristics on health and quality of life through transport-related physical activity levels was not found. Conclusions: Leisure-time physical activity instead of transport-related physical activity should be considered a priority when developing interventions aiming to promote healthy aging. Additionally, neighborhood characteristics are important in promoting healthy aging, even though they have no or less impacts on older adults' health and quality of life through physical activity.